Nonlinear and Adaptive Control Design - Krstic, Miroslav ((Adaptive and Learning Systems for Signal Processing, Communications, and Control))
Contenido: 1) Introducción; 2) Retroalimentación de estado; 3) Retroalimentación de salida. Apéndices.